The Value of Friendship in Animated Films Masha and The Bear: Semiotic Review - Thera Widyastuti; Kiki Srimayanti (Politeknik Negeri Media Kreatif, 2023)
Animated is one of the film genre that is used as a tool of education for children. One of the animated series that is popular in Indonesia is Masha and the Bear. The friendship that exists between Masha and the bear is closely related to each other. This research focuses on examining the story of Masha and the bear's friendship in the episode entitled